Desk review of school food environment literature, policy and guidelines in the Philippines - Umali, Diana Jean; Itliong, Kirstein; Anunciado, Ma. Shiela; Monville-Oro, Emilita; Gonsalves, Julian Francis; Hunter, Danny; Borelli, Teresa; Mendonce, Sharon (2023)
Schools are considered a favourable setting to promote greater consumption of fruits and vegetables among children and to shape a healthy food environment. This study aimed to characterise current school food environments in the Philippines, identify research gaps and develop recommendations to improve fruit and vegetable consumption among children.